(559) Information Retrieval; And Its Potential For Progress Of Research In The U.A.R استرجاع المعلومات وإمكاناته لدفع تقدم البحث في الجمهورية العربية المتحدة - A. Mongy, Mohamed; M. Elewa, Aida; ., and others (INP, 2024)
Information Retrieval and Its Potential for Research Progress in the U.A.R. This report explores the importance of information retrieval and its impact on advancing scientific research in the U.A.R., addressing the following topics: The Need for Information Retrieval: Mechanized Information Retrieval Systems: Practical Applications of Information Retrieval: Information Retrieval Potential in the U.A.R.: The role of national documentation and information centers. New applications for computer technologies.